2020
DOI: 10.1111/pbi.13286
|View full text |Cite
|
Sign up to set email alerts
|

Heritable temporal gene expression patterns correlate with metabolomic seed content in developing hexaploid oat seed

Abstract: Summary Oat ranks sixth in world cereal production and has a higher content of health‐promoting compounds compared with other cereals. However, there is neither a robust oat reference genome nor transcriptome. Using deeply sequenced full‐length mRNA libraries of oat cultivar Ogle‐C, a de novo high‐quality and comprehensive oat seed transcriptome was assembled. With this reference transcriptome and QuantSeq 3′ mRNA sequencing, gene expression was quantified during seed development from 22 diverse lines across s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 53 publications
0
32
0
Order By: Relevance
“…The current version (Avena sativa-OT3098 v1, PepsiCo) of the oat reference genome has been independently annotated by using transcripts from Hu et al (2020) and PacBio data generated by PepsiCo, respectively (see text footnote 1). Hence, transcripts from both sources between the flanking markers were retrieved.…”
Section: Candidate Genes For Dw6mentioning
confidence: 99%
See 2 more Smart Citations
“…The current version (Avena sativa-OT3098 v1, PepsiCo) of the oat reference genome has been independently annotated by using transcripts from Hu et al (2020) and PacBio data generated by PepsiCo, respectively (see text footnote 1). Hence, transcripts from both sources between the flanking markers were retrieved.…”
Section: Candidate Genes For Dw6mentioning
confidence: 99%
“…A total of 12 and 5 transcripts from Hu et al (2020) and PacBio data generated by PepsiCo were found within the region where Dw6 was mapped, respectively. After de-redundancy, nine transcripts were retained and BLASTN analyzed.…”
Section: Candidate Genementioning
confidence: 99%
See 1 more Smart Citation
“…Oat has a high content of health-promoting compounds such as unsaturated fatty acids, dietary fiber, antioxidants and vitamins, which makes it an interesting target for metabolomics studies from a human health and nutrition perspective (IMARC Group, 2019). In addition, high-density genetic markers have been developed in oat (Bekele et al, 2018), a draft genome sequence has been released (PepsiCo, 2020) and a high-quality and comprehensive seed transcriptome has been characterized (Hu et al, 2020). Furthermore, recent advances in high throughput sequencing and metabolite profiling technologies enable quantification of gene expression and metabolite abundance for hundreds of samples with high precision and reasonable cost (Alseekh & Fernie, 2018;Moll et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Precisely because gene expression datasets are typically large and noisy, they are ideal candidates for exceptionally large accuracy gains. As a representative example of gene expression data, this article uses data on oats from Hu et al (2019). The purpose of this experiment is to elucidate gene expression in developing hexaploid oat seeds so that oat breeders can release new cultivars with higher contents of health-promoting compounds, including avenanthramides that are reported to modulate signaling pathways associated with cancer, diabetes, inflammation, and cardiovascular disease.…”
mentioning
confidence: 99%